2021
DOI: 10.1037/cep0000256
|View full text |Cite
|
Sign up to set email alerts
|

It is not always a matter of time: Addressing the costs of metaphor and metonymy through a speed-accuracy trade-off study.

Abstract: One of the most debated topics in figurative language studies is whether the access to nonliteral meanings is direct or indirect. Although models that argue for longer processing times for figurative compared to literal meanings have been largely criticized, figurative language is often associated with increased cognitive work. We investigated whether such greater cognitive work is indicative of more time-consuming processes or rather lower availability of figurative meanings, and whether there are differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Producer-for-product metonymy (Dickens) has not revealed any differences in reading times (McElree et al, 2006), eye-tracking (Frisson & Pickering, 1999) or ERP research (Weiland-Breckle & Schumacher, 2017), as long as the source concept is known (see Frisson & Pickering, 1999, 2007 for studies with a newly introduced concept such as Needham as an author). A speed-accuracy trade-off study of producer-for-product metonymy showed a lower probability to arrive at a meaningful interpretation (asymptotic level) in comparison to the literal control reading, but no differences in processing dynamics (Bambini et al, 2021). Likewise, place-for-institution metonymy (the university called) as well as place-for-event metonymy (she protested during Vietnam) also registered no effects (Frisson & Pickering, 1999;Bott et al, 2016) nor did content-for-container metonymy (hand me the beer) (Schumacher, 2013).…”
Section: Real-time Comprehension Of Metonymymentioning
confidence: 88%
“…Producer-for-product metonymy (Dickens) has not revealed any differences in reading times (McElree et al, 2006), eye-tracking (Frisson & Pickering, 1999) or ERP research (Weiland-Breckle & Schumacher, 2017), as long as the source concept is known (see Frisson & Pickering, 1999, 2007 for studies with a newly introduced concept such as Needham as an author). A speed-accuracy trade-off study of producer-for-product metonymy showed a lower probability to arrive at a meaningful interpretation (asymptotic level) in comparison to the literal control reading, but no differences in processing dynamics (Bambini et al, 2021). Likewise, place-for-institution metonymy (the university called) as well as place-for-event metonymy (she protested during Vietnam) also registered no effects (Frisson & Pickering, 1999;Bott et al, 2016) nor did content-for-container metonymy (hand me the beer) (Schumacher, 2013).…”
Section: Real-time Comprehension Of Metonymymentioning
confidence: 88%
“…I follow influential scholarship (Gibbs, 1994;Coulson and Matlock, 2001;Camp, 2006c;Bambini and Resta, 2012;Weiland et al, 2014;Bambini et al, 2016Bambini et al, , 2021Rapp et al, 2018;Patalas and de Almeida, 2019;Pissani and de Almeida, 2022) in referring to this group as "direct access theorists". I acknowledge that there is a diversity of positions amassed under this banner.…”
Section: Introductionmentioning
confidence: 99%
“…Further inferences lead to the interpretation of the metaphor, for instance, 'Sally is inconsistent' or perhaps, in a different context, 'Sally is not reliable'. Thus, metaphor comprehension is derived through a series of pragmatic inferences that involve exploring the encyclopedic properties of lexical concepts and taking context into account (for a processing-oriented discussion of this account, see (Bambini et al, 2021)). This was the basis for our training strategy: we taught children how to adjust the lexical concepts by selecting the relevant properties and use the context in order to infer and explain the meanings of metaphors.…”
Section: Introductionmentioning
confidence: 99%